Environmental Epigenomics in Health and Disease Epigenetics and Disease Origins - Jirtle, Randy L.; Jirtle, Randy L.; Tyson, Frederick L.; Tyson, Frederick L. (Epigenetics and Human Health,, 2013)
Exposure to environmental toxicants is associated with changes in DNA methylation and gene expression profiles that together can contribute to increased disease susceptibility. The chapters in this volume, Environmental Epigenomics in Health and Disease - Epigenetics and Disease Origins, address a wide range of environmental exposures, such as airborne particulates, cocaine, radiation, tobacco smoke, and xenoestrogens. Particular emphasis is placed on the consequences of environmental exposures during development on epigenetic reprogramming that influences adult disease pathogenesis. Health outcomes associated with these exposures include autoimmune disorders, neurodevelopmental disorders, and cancer. Importantly, dietary supplements and drugs can modify the epigenetic effects induced by these agents, thereby reducing their toxicological impact. The overall purpose of this volume and its companion, Environmental Epigenomics in Health and Disease - Epigenetics and Complex Diseases, is to give readers an overview of how environmental exposures during early development can influence disease formation by disrupting epigenetic processes and developmental programming.